MiR-199b-5p enhances the proliferation of medullary thymic epithelial cells via regulating Wnt signaling by targeting Fzd6. (12th December 2020) - Wang, Xintong; Li, Ying; Gong, Bishuang; Zhang, Kaizhao; Ma, Yongjiang; Li, Yugu
Abstract: Thymic epithelial cells (TECs) are essential regulators of T-cell development and selection. miRNAs play critical roles in regulating TEC proliferation during the process of thymic aging. Our previous studies revealed that miR-199b-5p was upregulated in TECs from 1- to 3-month-old mice. But its function and potential mechanism are not clear. We hypothesized that miR-199b-5p may play an important role in age-related thymus involution via targeting some genes. To confirm it, the murine thymic epithelial cell line 1 (MTEC1) cells were used. Our results showed that overexpression of miR-199b-5p can enhance MTEC1 cell proliferation. On the contrary, repression of miR-199b-5p can inhibit MTEC1 cell proliferation. Meanwhile, it was confirmed that frizzled receptor 6 ( Fzd6 ) is the direct target gene of miR-199b-5p. Furthermore, overexpression of miR-199b-5p can upregulate the expressions of β-catenin, Tcf7, Wnt4, and C-myc to activate Wnt signaling and cell cycle signaling. Silence of Fzd6 and co-transfection with si Fzd6 and miR-199b-5p mimic/inhibitor confirmed that the biological function of miR-199b-5p is indeed by targeting Fzd6 in medullary TECs. Overall, miR-199b-5p is an important regulator in medullary TEC proliferation through targeting Fzd6 to activate Wnt signaling and cell cycle signaling. Our data indicate that miR-199b-5p may block the process of thymic aging and be a potential therapeutic target for thymus involution.